Arizona Education Tax Credit and Hidden Considerations of Justice - Moses, Michele S. (Education Policy Analysis Archives, 2000)
The current debate over market-based ideas for educational reform is examined, focusing specifically on the recent movement toward education tax credits. Viewing the Arizona education tax credit law as a voucher plan in sheep's clothing, I argue that the concept of justice underlying the law is a crucial issue largely missing from the school choice debate. I question the libertarian conception of justice assumed by voucher and tax credit advocates, and argue instead that a contemporary liberal democratic conception of justice ought to undergird attempts at school reform. A call for educators and policymakers to concentrate energies on efforts to help needy students rather than on efforts to channel tax dollars toward self- interested ends concludes the article.